3D interfacial geometries for co-optimized capacitance and mechanical properties in multi-material printing. (2022) - Tan, J.C.; Tan, M.C.; Low, H.Y.; Douarville-Blaise, J.P.; Matroja, R.; Charnace, H.G.
Abstract: Geometrical freedom in design brought upon by additive manufacturing (AM) has allowed for the fabrication of net shape object with complex geometry and more recently, functional multi-material parts. Multi-material printing of functional net shape objects has been demonstrated using combination of dissimilar materials. A common challenge in multi-material construct is the interfacial failure especially between dissimilar materials, and most reported work on multi-material printing have been limited to 2-D planar interface. In this work, we report the fused filament deposition (FDM) process of electrically conductive composite with an insulating polymer for a 3D capacitor, in which the interface geometry was designed to achieve maximum interfacial area between the two materials. Modelling of the 3-D interface geometry which is a periodic wave form with varying frequency, amplitude and curvature was conducted using Finite Element Analysis. FDM printed capacitors with the optimized 3D interfacial features showed an ∼8x increase in capacitance over similarly printed capacitor with planar interface design. Furthermore, the optimized 3D interface also resulted in an improved interfacial strength as demonstrated by a 3-point bending test. These 3D interfaces can be readily applied to 3D printed wearable/embedded electronics to improve upon their functionality and resistance to mechanical damage.